Т.МӘТМУРАТОВТЫҢ ВУЛЬГАРИЗМЛЕРДЕН ПАЙДАЛАНЫЎЫ - Бухарбаева, Ж.Ж. (SCIENCE and SOCIETY, 2022)
The article studied the and methodological application of vulgarisms used in the works of the poet T.Matmuratov. Also, the poet's works studied the attitude of vulgarism to the events and events of the characters.
Keywords: vulgarism; silence; insult; enmity